2011
DOI: 10.5009/gnl.2011.5.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Fermented Milk Containing Dietary Fiber Has Additive Effects in IBS with Constipation Compared to Plain Probiotic Fer-mented Milk

Abstract: Background/Aims: Although controversial, probiotics and dietary fiber are commonly used for patients with irritable bowel syndrome (IBS). We evaluated the effects of multistrain probiotics on the symptoms of IBS to determine whether the addition of dietary fi ber had an additive effect on constipation-predominant IBS. Methods: A total of 142 participants who met the Rome III criteria were recruited and randomized into a control group or a test group. Participants in the control group received multistrain probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…15 In a study by Choi SC, et al it was observed that probiotic fermented milk containing dietary fiber was more effective particularly in those patients with the constipation-predominant IBS. 16 The said study confirmed the available evidence that fiber appears to play a role in the management of patients with IBS, especially if constipation is the primary concern. Although insoluble fiber is not better than placebo but soluble fiber in particular showed favourable results in IBS related constipation.…”
Section: -14supporting
confidence: 74%
“…15 In a study by Choi SC, et al it was observed that probiotic fermented milk containing dietary fiber was more effective particularly in those patients with the constipation-predominant IBS. 16 The said study confirmed the available evidence that fiber appears to play a role in the management of patients with IBS, especially if constipation is the primary concern. Although insoluble fiber is not better than placebo but soluble fiber in particular showed favourable results in IBS related constipation.…”
Section: -14supporting
confidence: 74%
“…A number of multispecies LAB preparations (see Table S1 for list of LAB in mixtures), including VSL #3, have also demonstrated efficacy in the alleviation of abdominal pain . In contrast, many multispecies LAB trials, again including VSL #3, have not been able to demonstrate an effect of the LAB on abdominal pain …”
Section: Lab and Abdominal Pain/discomfort In Ibsmentioning
confidence: 99%
“…Of the multispecies LAB trials, VSL #3 has proved effective at reducing bloating in both adults (12 point improvement over placebo on 100 mm VAS) and children (0.55 point improvement over placebo on 0–4 Likert scale) although the benefit in adults was not demonstrated in a subsequent study . Of the other trials of multispecies bacteria where bloating/distension were assessed, two demonstrated positive effects, whereas another showed no improvement on this particular symptom …”
Section: Lab and Abdominal Bloating/distensionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first week of treatment, consumption of the test product appeared to be associated with a superior improvement in stool frequency and consistency, but during the second week of treatment, both treatments appeared to produce improvement in stool consistency. In South Korea, Choi et al46 randomly allocated 142 patients with constipation predominant IBS to receive either a multi-strain probiotic fermented milk with Streptococcus thermophilus , Lactobacillus acidophilus and Bifidobacterium infantis mixed with dietary fiber or the same probiotic fermented milk without fiber for 4 weeks. Superior improvement in stool frequency and straining were reported for the fiber-enhanced treatment.…”
Section: Dietary and Lifestyle Advicementioning
confidence: 99%